The Supreme Court and the sacrifice of animals in religions of african matrix: reflection on religious freedom that stem from Extraordinary Resource nº 494.601/RS (Research, Society and Development, 2021)
The Federative Republic of Brazil constitutes a secular state, that is, non-confessional, in a way that does not adopt an official religion. Unlike the Political Constitution of the Empire of Brazil of 1824, the Citizen Constitution 1988 establishes a clear separation between religion and state functions, since there can be no state interference in religion, nor will religion delimit any activity of the Republic. In this sense, freedom of religion will be preserved, in a pluralistic conception, to a point that everyone is guaranteed the right to assume a religious belief, to profess it publicly, as well as the right not to choose to practice any religion. However, the preamble to the Constitution contains the express mention of "God", which is why, at one point, it doubted the laicity of the Brazilian State. Thus, the issue of religions of African origin is added to this, from which the State of Rio Grande do Sul raised a relevant constitutional debate by editing the State Code of Animal Protection, excluding, in its art. 2nd, single paragraph, the illegality of animal sacrifice in rituals of this religious confession. Recognizing the membership of Afro-Brazilian religions by a minority of society, the Supreme Federal Court, in the exercise of the counter-majority function, in the case of Extraordinary Appeal No. 494.601/RS, decided on the constitutionality of animal protection law that allows the sacrifice of animals in religious rituals related to African culture, under the foundations articulated throughout this article, produced through qualitative research and based on bibliographic review methodology.